Technical and socio-economic characterization of small ruminants production systems in Saudi Arabia: results from a survey to stockbreeders - Aljumaah R.S.; Alshaikh M.A.; Alyemni A.H.; Ayadi M.; Sayadi S. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Based on a survey of 818 small ruminant breeders and on participative work performed in rural areas of the Kingdom of Saudi Arabia, this study describes the main characteristics of small ruminants herd structure and their productive and commercial problems. Therefore, some conclusions and recommendations are deduced for both improving the operation of these herds and to take full advantage of the potential of sheep and goat farming sector in the design of sustainable development policies for Saudi Arabian‘s rural areas.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)